Transformational practices in fifteenth-century German music - Lewon, M (2017)
In this thesis I investigate transformational practices in the secular music of mid-fifteenth-century German sources. At the heart of the research are case studies of the Lochamer Liederbuch with its two sections—a song and a keyboard collection—and of the newly discovered Wolfenbüttel Lute Tablature. By analysing and comparing the different versions of pieces surviving in these and related sources I explore how they interacted and what the motivations and techniques behind their transformation were. The organist and lute player Conrad Paumann and his ‘School’ were central driving forces in this process, which led to numerous innovations, particularly in the development of instrumental music and its notation. I then investigate the question of the instrumental accompaniment of monophonic song and how the development of new instruments and techniques influenced and shaped the melody types in the late medieval sources. To do this, I consult the genre of Neidhart songs as an oeuvre of secular song that was cultivated and transmitted in sources from the thirteenth to the fifteenth centuries. The network of interdependencies between repertoires enables an analysis of transformational practices in the songs of Oswald von Wolkenstein, which are influenced by the Neidhart-genre. The analysis comes full circle with reworkings of his melodies in the Lochamer Liederbuch and related sources. The study shows that vocal music and instrumental intabulations influenced each other mutually to create new repertoires and styles. Amongst the most significant insights are the findings around the Wolfenbüttel Lute Tablature, which open up a field of hitherto unknown instrumental practices and playing techniques, particularly on the plectrum lute. The process of transferring intabulation techniques from the keyboard to other polyphonic instruments leads to the formulation of a coherent, ‘pan-instrumental’ style of solo intabulation in the fifteenth century.